ДЖЕРЕЛА ДО ВИВЧЕННЯ ІСТОРІОГРАФІЇ НАЦІОНАЛЬНО-КУЛЬТУРНИХ ПРОЦЕСІВ В УКРАЇНІ 1920-х ñ ПОЧАТКУ 1930-х років (Zaporizhzhia Historical Review, 2021)
The author of the article analyses historical studies which light up national cultural processes in Soviet Ukraine in 20-30es of ХХ century. The author pointed out few groups of scientific literature related to outlined problematics and described each of them, marking features and informative saturation of each of them.